Մյուռոնօրհնության ծիսակարգը - Ազիզյան, Արամայիս սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье «Чин освящения Святого Мира: ритуально-исторический обзор» сделана попытка обрисовать ход исторического развития обряда освящения Святого Мира, сравнивая исторические источники, особенно рукописные и печатные каноны освящения Святого Мира. В этой статье впервые рассматри- ваются древнейшие известные нам чины освящения святого Мира (Антелиас № 9, ММ 4997, ММ 5702), раскрывающие истоки и процесс становления нынешнего обряда. Также сравнены обряды трех вышеупомянутых древнейших патриарших ритуальных книг «Маштоц» с канонами освящения Святого Мира, напечатанными в 1876 и 1890 годах в Вагаршапате, чтобы показать ход исторического развития чина освящения Святого Мира. In the article entitled «The Blessing Ceremony of the Holy Myron: Ritual- Historical Review», I tried to outline the historical development course of the blessing ceremony of the Holy Myron by comparing historical sources, especially the handwritten and printed canons of blessing the Holy Myron. In this article, for 19 the first time, the oldest rites of blessing the Holy Myron known to us (Antelias No. 9, MM 4997, MM 5702) are examined, revealing the origins and formation process of the current ceremony. I have also compared the rites of the three above-mentioned oldest Patriarchal “Mashtots” ritual books with the canons of blessing the Holy Myron printed in 1876 and 1890 in Vagharshapat to show the historical development course of the blessing ceremony of the Holy Myron.
Keywords: Կրօնագիտութիւն; Ծիսակատարութիւններ